Antioxidative properties of selected microencapsulated plants powder prepared using ultrasonic spray-drying technique - Mohamad Khairi Zainol,; Lew, Hew Wern; Nur Izzati Mohd Fauzi,; Ng, Khai Shin; Nurhakimah Razman,; Nur Fazila Kadimi,; Amir Izzwan Zamri,; Zamzahaila Mohd Zin,; Fisal Ahmad,; Tuan Zainazor Tuan Chilek,; Hasmadi Mamat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ultrasonic spray drier technology has been practice because of its numerous advantages, including providing more uniform droplets and reducing bioactive compounds damages. This study was aimed to measure the antioxidant properties of several microencapsulated plants powder (MPP) prepared using ultrasonic spray dying technique. The plant samples were treated using ultrasonic spray drier at 80°C inlet temperatures and 10% of gum Arabic relative to solid content. The collected MPP were analysed for their antioxidant activities. The plants use in this study were C. ternatea, M. indica, S. rebaudiana, P. macrocarpa, K. salvarezii and R. apiculata, All MPP showed somewhat very promising high antioxidative activities with C. ternatea significantly exhibited the highest (P<0.05) antioxidant power in nearly all antioxidative test analysis performed. On the other hand, M. indica showed the least ability in antioxidant power and the content of bioactive compounds. Results of the study point that the production of MPP and microcapsules is feasible as a functional ingredient in food industry as it can retain the antioxidative properties, which could lead to a more sustainable usage of natural resources.